Determination of total phenolic content in red and green cabbage by usingt two different solvents: ethanol and water / Ahmad Fauzi Abu Bakar - Abu Bakar, Ahmad Fauzi (Faculty of Applied Sciences, 2008)
Brassica oleracea or cabbage is a very popular plant among Malaysians. This project was carried out to determine the total phenolic content for cabbages in the local market after extraction with two different solvents which are water and ethanol. This project was carried out to obtain and differentiate the total phenolic content between red cabbage and green cabbage. The total phenolic content was determined using Folin-Ciocalteu reagent method based on the standard calibration curve of Gallic acid measured at 650 nm using UV-Visible Spectrometer (Perkin Elmer). The total phenolic content for red cabbage that extracted with water was 0.0150 mg/g GAE whereas for green cabbage that extracted with water was 0.0067 mg/g GAE. The total phenolic content for red cabbage that extracted with ethanol was 0.0016 mg/g GAE whereas the total phenolic content for green cabbage that extracted with ethanol was 0.0047 mg/g GAE. The research shown that the total phenolic content that soaked in water for both kinds of cabbage have the higher total phenolic content.